Optimalisasi Pencegahan Triple Burden pada Ibu Hamil Berbasis Flipbook Gizi 1.000 Hari Pertama Kehidupan di Desa Bangun Rejo - Mesrida Simarmata; Srininta Srininta; Ariska Fauzianty; Rolasnih Lilista Simbolon; Kamelia Sinaga; Rasmi Manullang; Eka Purnamasari; Yuliska Febriyan; Misno Misno (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Indonesia faces a triple burden of malnutrition, including anemia, chronic energy deficiency, and obesity among women. In 2024, anemia prevalence reached 30.7%, while SDG 2025 data reported that 28% of women experienced malnutrition. This study aimed to improve pregnant women’s knowledge of triple burden prevention through the "Nutrition for the First 1,000 Days of Life" flipbook in Bangun Rejo Village. A pre-experimental study was conducted from January to April 2026 involving 30 pregnant women selected through purposive sampling. The intervention consisted of socialization, training, technology implementation, mentoring, and evaluation. Knowledge was measured using a questionnaire and analyzed with the Wilcoxon Signed-Rank Test. Knowledge scores significantly improved after the intervention (p = 0.000; p < 0.05), demonstrating the effectiveness of the flipbook as a nutrition education medium. The flipbook effectively increased pregnant women’s knowledge regarding triple burden prevention. The flipbook should be utilized as an educational medium to improve maternal nutritional knowledge and support healthy pregnancy outcomes.